2021
DOI: 10.3892/or.2021.8171
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‑targeted microbubble destruction‑mediated overexpression of Sirtuin 3 inhibits the progression of ovarian cancer

Abstract: Ultrasound-targeted microbubble destruction (UTMD) has recently been developed as a promising noninvasive tool for organ-and tissue-specific gene or drug delivery. The aim of the present study was to explore the role of UTMD-mediated Sirtuin 3 (SIRT3) overexpression in the malignant behaviors of human ovarian cancer (HOC) cells. Reverse transcription-quantitative PCR was performed to detect SIRT3 mRNA expression levels in normal human ovarian epithelial cells and HOC cell lines; low SIRT3 expression was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…It was suggested that ultrasound-targeted microbubble destruction contributed to effective inhibition of Livin in ovarian cancer cells, resulting in accelerating cell apoptosis and reducing cell survival rate. These findings were similar to another study, indicating that overexpression of sirtuin-3 mediated by targeted microbubble destruction was helpful to inhibit the progression of ovarian cancer [ 32 ]. The research presented by Chen et al pointed out that ultrasound microbubble destruction targeting survivin induced apoptosis of HeLa cells in cervical cancer and led to inhibit the progression of cervical cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…It was suggested that ultrasound-targeted microbubble destruction contributed to effective inhibition of Livin in ovarian cancer cells, resulting in accelerating cell apoptosis and reducing cell survival rate. These findings were similar to another study, indicating that overexpression of sirtuin-3 mediated by targeted microbubble destruction was helpful to inhibit the progression of ovarian cancer [ 32 ]. The research presented by Chen et al pointed out that ultrasound microbubble destruction targeting survivin induced apoptosis of HeLa cells in cervical cancer and led to inhibit the progression of cervical cancer [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sirts are nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases that target a variety of protein substrates that has effects on oxidative stress regulation, metabolism, cell survival, division, and aging ( 124 , 125 ). Among the sirtuins, Sirt3, a genomically expressed, mitochondrial-located tumor suppressor protein has an aberrantly low level of expression in various cancers including OCs ( 126 128 ) where Sirt3 has anti-proliferative and anti-migratory effects. Sirt3 gene delivery by UTMD in vitro inhibited proliferation, epithelial-to-mesenchymal transition, and migration, and induced apoptosis and cell cycle arrest of SKOV3 cells.…”
Section: Us-mediated Delivery Of a Tumor Suppressor Proteinmentioning
confidence: 99%
“…Sirt3 gene delivery by UTMD in vitro inhibited proliferation, epithelial-to-mesenchymal transition, and migration, and induced apoptosis and cell cycle arrest of SKOV3 cells. Furthermore, UTMD delivery of Sirt3 in mice bearing SKOV3 xenograft tumor suppressed tumor volume and weight with an attendant decrease in Ki67 positive cells ( 126 ).…”
Section: Us-mediated Delivery Of a Tumor Suppressor Proteinmentioning
confidence: 99%